(untitled) (Current Horticulture, 2024)
About 153 wild plants were identified as edible used by tribals of the Andaman and Nicobar Islands, including 63 trees (2 small trees), 38 herbs, 23 shrubs, 16 climbers, 2 each creepers, twinners, grasses and sedges, and one each fern, vine and weed. Various parts of these plants were reported to be utilized as food, fruits, vegetables and utilized for making pickle/jam and jelly/beverages. Many tuber crops belonging to Dioscoreaceae family such as Dioscorea esculenta, D. glabra, D. pentaphylla and D. vexans are relished by the tribals. Therefore, conservation and enriching the population of these plants in tribal area is very important. The nutritional aspects and the presence of dangerous steroids in these plants if any have to be studied in detail.